A review of outcome measures used in cleft care. (June 2014) - Jones, Timothy; Al-Ghatam, Rana; Atack, Nikki; Deacon, Scott; Power, Rosie; Albery, Liz; Ireland, Tony; Sandy, Jonathan
Abstract : This article provides a summary of the main outcome measures currently available and in use within modern cleft care. The fact that there are such a diverse range, including surgical, orthodontic, dental, speech and patient satisfaction measures, is a reflection of the complex, multidisciplinary and longitudinal nature of the care provided. The use of such measures of outcome is essential in the auditing and drive for continued improvements in the standards of care for patients affected with cleft lip and palate.